Management effectiveness: Evaluating employees' perception on recruiting process at Lekor Shop in Shah Alam / Norfaezah Md Isa (Faculty of Business and Management, 2007)
This research is conducted in order to find out the most effective activities that the company does in order to maintain their effectiveness of the management. Besides that, it also to ensure all the existing activities is still relevant in the future time. In getting the data, 50 questionnaires were distributed to the selected respondents. The respondents are employees at Lekor Shop in Shah Alam. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability, frequency and descriptive. Several limitations were faced in completing in this study. Therefore, to obtain the correct sample size may required more times and effort which is beyond researcher capabilities and time frame given. Thus, recommendations are included in this project paper in order to help Lekor Shop to increase their management to more effective.